(untitled) (Nordic Journal of African Studies, 2005)
The present article tries to unravel how lexemes are sourced and meaning is encoded in Sheng. Sheng is a language variety that has been in use, especially among the urban youth in Kenya for over twenty years now. Whereas many of the surface morphemes of Sheng look like Kiswahili morphemes and thus lead to claims that Sheng is Kiswahili-based, counter-claims also exist. Some of the lexemes are alien to Kiswahili or any other language in the speech community where Sheng is spoken. In addition, it is difficult for the non-initiated, including Kiswahili speakers, to follow a conversation in Sheng. Against this background, an attempt is made to unravel the source(s) of Sheng lexemes and to trace the diachronic changes that have taken place where a concept has been represented by more than one lexeme. Above all, the paper attempts to deconstruct the logic and essence of embedding sense in the Sheng lexemes.